Copper metabolism and hepatocellular carcinoma: current insights - Zhou, Cheng; Yang, Jinqiu; Liu, Tong; Jia, Ran; Yang, Lin; Sun, Pengfei; Zhao, Wenxia (Frontiers in Oncology, 2023)
Copper is an essential trace element that acts as a cofactor in various enzyme active sites in the human body. It participates in numerous life activities, including lipid metabolism, energy metabolism, and neurotransmitter synthesis. The proposal of "Cuproptosis" has made copper metabolism-related pathways a research hotspot in the field of tumor therapy, which has attracted great attention. This review discusses the biological processes of copper uptake, transport, and storage in human cells. It highlights the mechanisms by which copper metabolism affects hepatocellular carcinogenesis and metastasis, including autophagy, apoptosis, vascular invasion, cuproptosis, and ferroptosis. Additionally, it summarizes the current clinical applications of copper metabolism-related drugs in antitumor therapy.